Effect of Ascorbic acid on the sensitivity of Salmonella typhi to antibiotics - Dhuha Mohamed; Bushra . Hamad; Muhsin Essa (College of Education for Pure Sciences, 2019)
This study included the investigation of the  effect of Ascorbic acid  (Vitamin C) and incubation at temperature of 44 C° on the sensitivity of Salmonella typhi to some antibiotics to which resistant it was Resistant Results showed that Ascorbic acid had a curing impact in removal of resistance character against many antibiotics (Amikacin Erythromycin ,Tobramycin, Penicillin ). Concentration of Ascorbic acid had a role in its effectiveness and the concentration (1.5) mM  was the best in all curing results. The study also demonstrated that the temperature 44c° had a curing effect on the resistance of bacteria under to most studied antibiotics except erythromycin according  to this results and because Ascorbic acid is not toxic, it be used with antibiotics against infection with  Salmonella typhi .